Axial Compression of Glass Fiber Tube-Gangue Concrete-Steel Tubular Hollow Columns - Ni Zhang; Chenyang Zheng; Zhongwei Zhao; Bo Yang (Advances in Materials Science and Engineering)
The replacement of coal gangue for aggregate in concrete can not only reduce the construction cost but also improve the environmental condition. The GFRP-coal gangue concrete-steel tubular (GGCS) columns provide a way to consume the coal gangue. The target of this work is to validate the feasibility of replacing ordinary concrete with coal gangue concrete and investigate the compression behavior of GGCS columns. The nonlinear analysis program of GGCS hollow columns under axial compression was proposed, and the axial compression tests of seven GGCS hollow columns were carried out. The program was verified through experimental results. On the basis of the correctness of the program, the influences of the typical parameters, such as the thickness of the glass fiber tube, the thickness of the steel tube, and the outer radius of the steel tube, on its axial compression performance were systematically analyzed. Finally, the analytical formula for predicting the axial bearing capacity of GGCS hollow column was proposed. The comparison of results indicated that the analytical results agreed well with the experimental results. The axial compression capacity of GGCS hollow columns increased linearly with the increase of the thickness of the glass fiber tube and the steel tube, but not linearly with the decrease of the outer radius of the steel tube. With the increase of the thickness of the glass fiber tube, the constraint effect of the glass fiber tube on gangue concrete was improved. With the increase of the thickness of the steel tube, the stiffness of GGCS hollow column increased. The conclusions of the presented work can provide references for the design and calculation of the GGCS columns.